Joie et deuil dans les Bestiaires des xiie et xiiie siècles : le cygne et le rossignol - Jean-Marie Fritz (Revue des Langues Romanes)
The nightingale, a bird central to the lyric of oc and oïl, has a complex and ambiguous relationship with joy: it is first of all the bird linked with the spring, immersing the poet in joy; conversely, it is also the one who sings with so much fervor that it dies while singing. The gentle death of the nightingale by dint of singing echoes that of the cicada or the cricket in the bestiaries of the Middle Ages or that of the swan, whose funeral song is also paradoxically a song of joy.